2020
DOI: 10.1111/cup.13652
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastasis of SMARCA4‐deficient thoracic sarcoma: A diagnostic dilemma with therapeutic implications

Abstract: SMARCA4-deficient thoracic sarcoma (SMARCA4-DTS) is a recently recognized entity with undifferentiated rhabdoid morphology and mutations in the switch/ sucrose nonfermenting BRG1-associated factors complex. Patients are typically males in their fifth decade with a history of smoking who present with rapidly progressive intrathoracic disease and follow an aggressive clinical course. Metastatic disease is reported in up to 77% of cases; however, to our knowledge, cutaneous metastasis has not been reported nor ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Patients were strongly associated with smoking and were predominantly male, and our cases t these demographic characteristics. SMARCA4-UT is an aggressive tumor with a poor prognosis, often metastasizing to the lymph nodes, adrenal glands, brain, and so on [11][12] . The patient's symptoms are one of the most interesting aspects of this case and an important diagnostic challenge in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were strongly associated with smoking and were predominantly male, and our cases t these demographic characteristics. SMARCA4-UT is an aggressive tumor with a poor prognosis, often metastasizing to the lymph nodes, adrenal glands, brain, and so on [11][12] . The patient's symptoms are one of the most interesting aspects of this case and an important diagnostic challenge in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, immunohistochemical screening using multiple antibodies including SMARCA4 and SOX2 is necessary to diagnose SMARCA4-UT [ 16 , 25 ]. Useful markers for diagnosis include immunopositivity for EMA, CD34, SALL4, and SOX2, and loss of expression of SMARCA2 [ 26 , 27 ]. In addition, Leckey et al[ 26 ] found that p40 and p63 were rarely expressed in SMARCA4-UT.…”
Section: Introductionmentioning
confidence: 99%
“…Useful markers for diagnosis include immunopositivity for EMA, CD34, SALL4, and SOX2, and loss of expression of SMARCA2 [ 26 , 27 ]. In addition, Leckey et al[ 26 ] found that p40 and p63 were rarely expressed in SMARCA4-UT. The immunohistochemical results of SMARCA4-UT are shown in Table 1 [ 5 , 9 , 14 , 15 , 17 , 23 26 , 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations